Development Of Ispring-Based Gamavak Interactive Media to Improve Student Learning Outcomes in Terms of Learning Styles - Serli Emiliana koehtae; Wahyudi Wahyudi; Kriswandani Kriswandani (Postgraduate, University of Mataram, 2025)
This study aims to develop iSpring-based GAMAVAK interactive media to improve student learning outcomes in terms of the learning styles of fifth-grade elementary schools. The background of this study includes the limitations of the use of technology and learning media that can involve students directly, low student learning outcomes due to the application of inappropriate learning styles with student characteristics, low student interest in learning mathematics due to students not being directly involved in learning, the need to increase interactivity in mathematics learning and adjustments to the curriculum. The method used is Research & Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The validation results from media experts, material experts and learning experts show that the developed media is very valid, with a score of 91%. The media includes competencies and learning objectives, systematic presentation, display quality, instructional quality, technical quality of the media, suitability of material content, suitability of problem solving, content and suitability with the principles of preparing teaching modules so that the media is classified as very feasible. The practicality test obtained a teacher response of 94% and students of 96%, indicating a very practical category. The improvement in learning outcomes was proven by a paired sample t-test with a significance value of 0.000 < 0.05 and t count 7.882 > t table 2.093, so that Ho was rejected and Ha was accepted. Thus, there was a significant difference between student learning outcomes before and after using GAMAVAK interactive media